A low-viscosity and high-strength cement-based grouting material and preparation method thereof
By using modified microbeads and micro-nano coagulant in cement-based grouting materials, the problems of high viscosity, poor injectability and insufficient strength of cement slurry in the prior art are solved, and low viscosity and high strength grouting materials are realized, which improves the safety and environmental protection performance of engineering applications.
Patent Information
- Application Number
- CN202411177090.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-08-26
AI Technical Summary
When existing cement-based grouting materials reduce the viscosity of cement slurry and improve the injectability, it is difficult to maintain the strength of cement stone, and commonly used grouting materials are costly, poorly operated and have the risk of environmental pollution.
The cement-based grouting material containing modified microbeads and micro-nano coagulant is used to hydroxylate the fly ash microbeads through alkali liquid to make their surface rich in hydroxyl groups, thereby fully and evenly distributing it in the grouting material, reducing the viscosity of the cement slurry, and forming a micro-nano coagulant through the reaction of gypsum and aluminum sulfate, improving the early strength of the grouting material.
While reducing the cement slurry water-cement ratio, the strength of cement stone is maintained, the insufficiency and early reinforcement effect of grouting materials are improved, and the cost of materials is reduced and environmentally friendly performance is enhanced.
Smart Images

Figure CN118993653B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of special cement-based materials, and in particular to a low-viscosity and high-strength cement-based grouting material and a preparation method thereof. Background Art
[0002] As infrastructure construction expands to the west, highway and railway construction has experienced rapid expansion. However, the complex and diverse geology in the western region has brought many thorny problems to the advancement of the project. The water-rich sandy soil layer is located below the groundwater level. The soil is broken and diverse, and the soil has a certain cohesive force under the action of self-weight stress. Therefore, it has poor injectability and is difficult to manage. If not handled properly, it is easy to cause sudden water and mud, landslides, and even mudslides, which not only delay construction, but may even cause great losses. Grouting can strengthen the soil layer to prevent sudden water and other disasters, and is widely used in transportation, railways, water conservancy projects, mining construction and other fields.
[0003] At present, the commonly used grouting materials are cement slurry and cement-water glass double slurry. In order to ensure that the slurry has good injectability, a larger water-cement ratio is often adopted in engineering. Although increasing the water-cement ratio can reduce the viscosity of the cement slurry and improve injectability, it will also cause the strength of the cement stone to decrease after hardening, and it will not be able to provide effective support, resulting in engineering accidents such as collapse of the face after excavation, ground collapse, and tunnel collapse. Although chemical grouting materials have good injectability and strength, they are expensive, poor in operability, highly toxic, and pollute the environment. Summary of the invention
[0004] In view of the above problems, the present invention discloses a low-viscosity and high-strength cement-based grouting material and a preparation method thereof, which reduces the water-cement ratio of cement slurry and ensures the strength of cement stone while reducing the viscosity of cement slurry and improving injectability. To achieve the above objectives, the present invention discloses the following technical solutions.
[0005] In the first aspect, the present invention discloses a low-viscosity and high-strength cement-based grouting material, comprising the following components: 300-600 parts of a cementitious material having volcanic ash properties, 0.2-0.6 parts of a micro-nano coagulant, 0.25-2% of the mass of the cementitious material by weight of a water-reducing agent, and a water-cement ratio of 0.4-0.8. The cementitious material having volcanic ash properties comprises silicate cement and modified microspheres, and the modified microspheres are 10-50% of the mass of the silicate cement.
[0006] The modified microbeads are prepared by the following method: (1) hydroxylating the fly ash microbeads with an alkali solution, adding the obtained fly ash microbeads to a dispersion formed by a silane coupling agent, a dispersant and anhydrous ethanol, separating the solid product, washing and drying, and obtaining the modified microbeads.
[0007] The micro-nano coagulant is prepared by the following method: (i) gypsum and alkali solution are mixed evenly to form a turbid liquid. (ii) silane coupling agent, dispersant and aluminum sulfate solution are mixed to form a modified liquid. (iii) the modified liquid is added to the turbid liquid and stirred for reaction. After completion, a solid product is separated, washed and dried to obtain the micro-nano coagulant.
[0008] Furthermore, in step (1), the treatment method is: mixing the fly ash microbeads with alkaline solution and then keeping the mixture warm under heating conditions, and after completion, separating the fly ash microbeads, washing them and then drying them.
[0009] Furthermore, the ratio of the fly ash microspheres to the alkali solution is 1g: 6-10ml. Optionally, the heating temperature is 40-45°C, and the insulation time is 1.5-2h.
[0010] Further, the alkali solution includes at least one of sodium hydroxide, potassium hydroxide, etc. Optionally, the concentration of the alkali solution is 0.1-0.5 mol / L.
[0011] Furthermore, in step (1), the mass ratio of the silane coupling agent, the dispersant, and the anhydrous ethanol is 1:0.2~0.3:120~150.
[0012] Furthermore, in step (1), the silane coupling agent includes at least one of γ-methacryloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, vinyltrimethoxysilane, etc.
[0013] Furthermore, in step (1), the dispersant includes at least one of triethylhexyl phosphoric acid, sodium dodecyl sulfate, etc.
[0014] Furthermore, in step (1), the ratio of the fly ash microbeads to the dispersion liquid is 1 g: 10-20 ml.
[0015] Furthermore, in step (i), the ratio of gypsum to alkali solution is 37g:100-120ml. Optionally, the alkali solution includes at least one of sodium hydroxide and potassium hydroxide. The mass fraction of the alkali solution is 0.4-0.6%.
[0016] Furthermore, in step (ii), the mass ratio of the silane coupling agent, the dispersant, and the aluminum sulfate solution is 4-6:1:105-115. Optionally, the mass fraction of the aluminum sulfate solution is 10-15%.
[0017] Furthermore, in step (ii), the silane coupling agent includes at least one of vinyl triethoxysilane, γ-aminopropyl triethoxysilane, octadecyl trimethoxysilane, and the like.
[0018] Furthermore, in step (ii), the dispersant includes at least one of a polycarboxylic acid dispersant and hydroxyethylidene diphosphonic acid.
[0019] Furthermore, in step (iii), the modified liquid is added to the turbid liquid in a molar ratio of gypsum to aluminum sulfate of 6:1.
[0020] Furthermore, in step (iii), the stirring reaction is carried out at a temperature of 55-65° C. and for a time of 11-13 hours.
[0021] Furthermore, the silicate cement includes: silicate cement is at least one of P·I 42.5, P·I 52.5R and the like.
[0022] Furthermore, the water reducer includes at least one of naphthalene water reducer, polycarboxylic acid water reducer, melamine water reducer, etc. The water reducer can release free water in the flocculation structure between cement particles, further reduce the viscosity of cement slurry, and make the cement slurry still have good injectability at a smaller water-cement ratio.
[0023] In a second aspect, the present invention discloses a method for preparing the low-viscosity and high-strength cement-based grouting material, comprising the following steps: uniformly mixing the gelling material with volcanic ash properties and the micro-nano coagulant, then adding a mixed solution formed by the water reducer and water, and stirring uniformly to obtain the cement-based grouting material.
[0024] Compared with the prior art, the present invention has at least the following beneficial technical effects:
[0025] The present invention achieves the goal of reducing the water-cement ratio of cement slurry and ensuring the strength of cement stone while reducing the viscosity of cement slurry and improving injectability by using cement-based grouting materials containing modified microspheres and micro-nano coagulants. The reason is that: on the one hand, the present invention first uses alkali solution to hydroxylate the fly ash microspheres, so that the surface of the fly ash microspheres is rich in hydroxyl groups, so that the silane coupling agent is grafted to the fly ash microspheres, so that the fly ash microspheres can be fully and evenly distributed in the grouting material, so that the ball effect can be fully exerted during grouting to reduce the viscosity of the cement slurry. In addition, the fly ash microspheres after hydroxylation can also use the calcium hydroxide produced by the hydration of the silicate cement to carry out hydration reaction to form a gelling component, thereby alleviating the decrease in the mechanical strength of the grouting material caused by the relatively low hydration degree of the fly ash microspheres, and compensating for the strength loss to a certain extent. On the other hand, the present invention uses a turbid liquid formed by gypsum and alkali solution and a modified liquid formed by a silane coupling agent, a dispersant, and an aluminum sulfate solution to prepare the micro-nano coagulant. In this process, gypsum and aluminum sulfate react to form calcium sulfonate crystals. Since the dispersant is adsorbed on its surface and dehydration condensation reaction occurs with the silane coupling agent, the crystal growth is inhibited. On the other hand, since the alkali solution in the turbid liquid plays a role of neutralization reaction with the acid produced, the pH value of the turbid liquid is maintained at a higher range, thereby limiting the growth of the crystals and forming a large number of fine grains. When this micro-nano coagulant is added to the grouting material, the nucleation barrier can be effectively reduced, the hydration of cement particles can be accelerated, the hydration products can be precipitated and overlapped to form a stable skeleton system, and the early strength of the grouting material can be improved, thereby improving the early reinforcement effect. In addition, the grouting material of the present invention is more environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. The embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein:
[0027] Figure 1 This is a sample picture of the low-viscosity and high-strength cement-based grouting material prepared in the following Example 1.
[0028] Figure 2 This is a flow time test diagram of the following Example 1. DETAILED DESCRIPTION
[0029] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or according to the conditions recommended by the manufacturer.
[0030] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. The low-viscosity and high-strength cement-based grouting material and preparation method of the present invention are further described in conjunction with the accompanying drawings and specific embodiments of the present invention.
[0031] Example 1
[0032] A low-viscosity and high-strength cement-based grouting material and a preparation method thereof, comprising the following steps:
[0033] 1. Preparation of modified microbeads:
[0034] (1) A 0.2 mol / L potassium hydroxide solution and fly ash microbeads were mixed evenly in a ratio of 6 ml:1 g and kept at 40°C for 2 hours. The microbead particles were then filtered out, washed with deionized water, and dried in an oven at 100°C for 4 hours to obtain hydroxylated fly ash microbeads.
[0035] (2) γ-aminopropyltriethoxysilane, triethylhexylphosphoric acid and anhydrous ethanol were mixed in a mass ratio of 1:0.3:150 and stirred evenly. Then, the hydroxylated fly ash microbeads of this embodiment were added in a solid-liquid ratio of 1 g:15 ml. After stirring evenly, the solid product was filtered out and placed in an oven at 100° C. to dry for 6 h to obtain modified fly ash microbeads for later use.
[0036] 2. Preparation of micro-nano coagulant:
[0037] (i) Mix dihydrate gypsum and 0.5% NaOH solution in a ratio of 37 g:100 mL and stir evenly to obtain a turbid solution for later use.
[0038] (ii) γ-aminopropyltriethoxysilane, polycarboxylic acid dispersant (maleic acid-acrylic acid copolymer (MA / AA)), and 10% by mass aluminum sulfate solution are mixed in a mass ratio of 5:1:112 and stirred evenly to obtain a modified solution for later use.
[0039] (iii) Add the modified liquid to the turbid liquid in a molar ratio of 6:1 between the dihydrate gypsum and aluminum sulfate, and then heat to 60°C and stir to react for 12 hours. After completion, filter out the solid product, wash it twice with deionized water, and dry it in an oven at 80°C for 10 hours to obtain a micro-nano coagulant.
[0040] 3. Take the following raw materials: 400 parts by weight of a cementitious material with volcanic ash properties (composed of 350 parts of silicate cement (P·I42.5) and 50 parts of the modified microspheres prepared in this embodiment), 0.4 parts by weight of the micro-nano coagulant prepared in this embodiment, 3 parts by weight of a polycarboxylate water reducer, and 160 parts by weight of water. First, mix the cementitious material and the micro-nano coagulant evenly, then add the mixture formed by the water reducer and water, and stir evenly to obtain the cement-based grouting material, such as Figure 1 shown.
[0041] Performance test: (1) The flow time of the cement-based grouting material prepared in this embodiment was tested using a 6-cup coating (e.g. Figure 2 As shown in Table 1), the viscosity / injectability of the grouting material is measured. The shorter the flow time, the lower the viscosity of the grouting material and the better the injectability. Conversely, the worse the injectability of the grouting material (the same below). (2) According to the "Test Method for Strength of Cement Mortar (ISO Method)" (GB / T 17671-2021), the 3d compressive strength of the cement-based grouting material prepared in this embodiment is tested. The test results are shown in Table 1:
[0042] Table 1
[0043] .
[0044] Example 2
[0045] A low-viscosity and high-strength cement-based grouting material and a preparation method thereof, comprising the following steps:
[0046] 1. Preparation of modified microbeads:
[0047] (1) 0.1 mol / L potassium hydroxide solution and fly ash microbeads were mixed evenly in a ratio of 10 ml:1 g and kept at 45 °C for 1.5 hours. The microbead particles were then filtered out, washed with deionized water, and dried in an oven at 80 °C for 5 hours to obtain hydroxylated fly ash microbeads.
[0048] (2) γ-methacryloxypropyltrimethoxysilane, sodium dodecyl sulfate and anhydrous ethanol were mixed in a mass ratio of 1:0.25:130 and stirred evenly. Then, the hydroxylated fly ash microbeads of this embodiment were added in a solid-liquid ratio of 1 g:10 ml. After stirring evenly, the solid product was filtered out and placed in an oven at 80°C for 6 hours to obtain modified fly ash microbeads for later use.
[0049] 2. Preparation of micro-nano coagulant:
[0050] (i) Mix dihydrate gypsum and 0.4% NaOH solution in a ratio of 37 g:120 mL and stir evenly to obtain a turbid solution for later use.
[0051] (ii) Octadecyltrimethoxysilane, hydroxyethylidene diphosphoric acid and 10% aluminum sulfate solution are mixed in a mass ratio of 6:1:115 and stirred evenly to obtain a modified solution for later use.
[0052] (iii) Add the modified liquid to the turbid liquid in a molar ratio of 6:1 between the dihydrate gypsum and aluminum sulfate, and then heat to 55°C and stir to react for 13 hours. After completion, filter out the solid product, wash it twice with deionized water, and dry it in an oven at 80°C for 10 hours to obtain the micro-nano coagulant.
[0053] 3. Take the following raw materials: 600 parts by weight of a cementitious material with volcanic ash properties (composed of 400 parts of Portland cement (P·I42.5) and 200 parts of the modified microspheres prepared in this embodiment), 0.4 parts by weight of the micro-nano coagulant prepared in this embodiment, 12 parts by weight of a polycarboxylate water reducer, and 480 parts by weight of water. First, mix the cementitious material and the micro-nano coagulant evenly, then add the mixed solution formed by the water reducer and water, and stir evenly to obtain the cement-based grouting material.
[0054] Performance test: (1) The flow time of the cement-based grouting material prepared in this embodiment was tested using a 6-cup coating to measure the viscosity / injectability of the grouting material. (2) The 3d compressive strength of the cement-based grouting material prepared in this embodiment was tested according to the "Test Method for Strength of Cement Mortar (ISO Method)" (GB / T 17671-2021). The test results are shown in Table 2:
[0055] Table 2
[0056] .
[0057] Example 3
[0058] A low-viscosity and high-strength cement-based grouting material and a preparation method thereof, comprising the following steps:
[0059] 1. Preparation of modified microbeads:
[0060] (1) 0.5 mol / L sodium hydroxide solution and fly ash microbeads were mixed evenly in a ratio of 7 ml:1 g and kept at 40°C for 2 hours. The microbead particles were then filtered out, washed with deionized water, and dried in an oven at 100°C for 4 hours to obtain hydroxylated fly ash microbeads.
[0061] (2) Vinyltrimethoxysilane, triethylhexylphosphoric acid and anhydrous ethanol were mixed in a mass ratio of 1:0.2:120 and stirred evenly. Then, the hydroxylated fly ash microbeads of this embodiment were added in a solid-liquid ratio of 1 g:20 ml. After stirring evenly, the solid product was filtered out and placed in an oven at 100° C. for 6 h to obtain modified fly ash microbeads for later use.
[0062] 2. Preparation of micro-nano coagulant:
[0063] (i) Mix dihydrate gypsum and 0.6% KOH solution in a ratio of 37 g:110 mL and stir evenly to obtain a turbid solution for later use.
[0064] (ii) Vinyl triethoxysilane, polycarboxylic acid dispersant (maleic acid-acrylic acid copolymer (MA / AA)), and 15% by mass aluminum sulfate solution are mixed in a mass ratio of 4:1:105 and stirred evenly to obtain a modified solution for later use.
[0065] (iii) Add the modified liquid to the turbid liquid in a molar ratio of 6:1 between the dihydrate gypsum and aluminum sulfate, and then heat to 65° C. and stir to react for 11 hours. After completion, filter out the solid product, wash it twice with deionized water, and dry it in an oven at 80° C. for 10 hours to obtain the micro-nano coagulant.
[0066] 3. Take the following raw materials: 300 parts by weight of a cementitious material with volcanic ash properties (composed of 272.7 parts of Portland cement (P·I 52.5R) and 27.3 parts of the modified microspheres prepared in this embodiment), 0.4 parts by weight of the micro-nano coagulant prepared in this embodiment, 0.75 parts by weight of a polycarboxylate water reducer, and 180 parts by weight of water. First, mix the cementitious material and the micro-nano coagulant evenly, then add the mixed solution formed by the water reducer and water, and stir evenly to obtain the cement-based grouting material.
[0067] Performance test: (1) The flow time of the cement-based grouting material prepared in this embodiment was tested using a 6-cup coating to measure the viscosity / injectability of the grouting material. (2) The 3d compressive strength of the cement-based grouting material prepared in this embodiment was tested according to the "Test Method for Strength of Cement Mortar (ISO Method)" (GB / T 17671-2021). The test results are shown in Table 3:
[0068] Table 3
[0069] .
[0070] Example 4
[0071] A low-viscosity and high-strength cement-based grouting material and a preparation method thereof, comprising the following steps:
[0072] (1) Take the following raw materials: 400 parts by weight of Portland cement (P·I 42.5), 0.4 parts by weight of the micro-nano coagulant prepared in Example 1, 3 parts by weight of polycarboxylate water reducer, and 160 parts by weight of water.
[0073] (2) First, the silicate cement and the micro-nano coagulant are mixed evenly, and then a mixed solution formed by the water reducer and water is added and stirred evenly to obtain the cement-based grouting material.
[0074] Performance test: (1) The flow time of the cement-based grouting material prepared in this embodiment was tested using a 6-cup coating to measure the viscosity / injectability of the grouting material. (2) The 3d compressive strength of the cement-based grouting material prepared in this embodiment was tested according to the "Test Method for Strength of Cement Mortar (ISO Method)" (GB / T 17671-2021). The test results are shown in Table 4:
[0075] Table 4
[0076] .
[0077] Example 5
[0078] A low-viscosity and high-strength cement-based grouting material and a preparation method thereof, comprising the following steps:
[0079] (1) Take the following raw materials: 600 parts by weight of a cementitious material having pozzolanic properties (composed of 400 parts of Portland cement (P·I 42.5) and 200 parts of the modified microspheres prepared in Example 2), 12 parts by weight of a polycarboxylate water-reducing agent, and 480 parts by weight of water.
[0080] (2) Adding a mixed solution formed by the water reducer and water into the cementitious material and stirring the mixture evenly to obtain the cement-based grouting material.
[0081] Performance test: (1) The flow time of the cement-based grouting material prepared in this embodiment was tested using a 6-cup coating to measure the viscosity / injectability of the grouting material. (2) The 3d compressive strength of the cement-based grouting material prepared in this embodiment was tested according to the "Test Method for Strength of Cement Mortar (ISO Method)" (GB / T 17671-2021). The test results are shown in Table 5:
[0082] Table 5
[0083] .
[0084] Example 6
[0085] A low-viscosity and high-strength cement-based grouting material and a preparation method thereof, comprising the following steps:
[0086] 1. Preparation of modified microbeads: γ-methacryloxypropyltrimethoxysilane, sodium dodecyl sulfate and anhydrous ethanol were mixed in a mass ratio of 1:0.25:130 and stirred evenly, and then the fly ash microbeads without any modification in this embodiment were added in a solid-liquid ratio of 1g:10ml. After stirring evenly, the solid product was filtered out and placed in an oven at 80°C for 6h to obtain modified fly ash microbeads for later use.
[0087] 2. Take the following raw materials: 600 parts by weight of a cementitious material with volcanic ash properties (composed of 400 parts of Portland cement (P·I42.5) and 200 parts of the modified microspheres prepared in this embodiment), 0.4 parts by weight of the micro-nano coagulant prepared in the above embodiment 2, 12 parts by weight of a polycarboxylate water reducer, and 480 parts by weight of water. First, mix the cementitious material and the micro-nano coagulant evenly, then add the mixed solution formed by the water reducer and water, and stir evenly to obtain the cement-based grouting material.
[0088] Performance test: (1) The flow time of the cement-based grouting material prepared in this embodiment was tested using a 6-cup coating to measure the viscosity / injectability of the grouting material. (2) The 3d compressive strength of the cement-based grouting material prepared in this embodiment was tested according to the "Test Method for Strength of Cement Mortar (ISO Method)" (GB / T 17671-2021). The test results are shown in Table 6:
[0089] Table 6
[0090] .
[0091] Example 7
[0092] A low-viscosity and high-strength cement-based grouting material and a preparation method thereof, comprising the following steps:
[0093] 1. Preparation of modified microbeads:
[0094] (1) 0.5 mol / L sodium hydroxide solution and fly ash microbeads were mixed evenly in a ratio of 7 ml:1 g and kept at 40°C for 2 hours. The microbead particles were then filtered out, washed with deionized water, and dried in an oven at 100°C for 4 hours to obtain hydroxylated fly ash microbeads.
[0095] (2) Triethylhexyl phosphoric acid and anhydrous ethanol were mixed at a mass ratio of 0.2:120 and stirred evenly. Then, the hydroxylated fly ash microbeads of this embodiment were added at a solid-liquid ratio of 1 g:20 ml. After stirring evenly, the solid product was filtered out and placed in an oven at 100° C. for 6 h to obtain modified fly ash microbeads for later use.
[0096] 2. Take the following raw materials: 300 parts by weight of a cementitious material with volcanic ash properties (composed of 272.7 parts of Portland cement (P·I 52.5R) and 27.3 parts of the modified microspheres prepared in this embodiment), 0.4 parts by weight of the micro-nano coagulant prepared in the above embodiment 3, 0.75 parts by weight of a polycarboxylate water reducer, and 180 parts by weight of water. First, mix the cementitious material and the micro-nano coagulant evenly, then add the mixed solution formed by the water reducer and water, and stir evenly to obtain the cement-based grouting material.
[0097] Performance test: (1) The flow time of the cement-based grouting material prepared in this embodiment was tested using a 6-cup coating to measure the viscosity / injectability of the grouting material. (2) The 3d compressive strength of the cement-based grouting material prepared in this embodiment was tested according to the "Test Method for Strength of Cement Mortar (ISO Method)" (GB / T 17671-2021). The test results are shown in Table 7:
[0098] Table 7
[0099] .
[0100] Example 8
[0101] A low-viscosity and high-strength cement-based grouting material and a preparation method thereof, comprising the following steps:
[0102] 1. Preparation of micro-nano coagulant:
[0103] (i) Mix dihydrate gypsum and 0.4% NaOH solution in a ratio of 37 g:120 mL and stir evenly to obtain a turbid solution for later use.
[0104] (ii) Mix hydroxyethylidene diphosphonic acid and 10% aluminum sulfate solution in a mass ratio of 1:115 and stir evenly to obtain a modified solution for later use.
[0105] (iii) Add the modified liquid to the turbid liquid in a molar ratio of 6:1 between the dihydrate gypsum and aluminum sulfate, and then heat to 55°C and stir to react for 13 hours. After completion, filter out the solid product, wash it twice with deionized water, and dry it in an oven at 80°C for 10 hours to obtain the micro-nano coagulant.
[0106] 2. Take the following raw materials: 600 parts by weight of a cementitious material with volcanic ash properties (composed of 400 parts of Portland cement (P·I42.5) and 200 parts of the modified microspheres prepared in Example 2 above), 0.4 parts by weight of the micro-nano coagulant prepared in this example, 12 parts by weight of a polycarboxylate water reducer, and 480 parts by weight of water. First, mix the cementitious material and the micro-nano coagulant evenly, then add the mixed solution formed by the water reducer and water, and stir evenly to obtain the cement-based grouting material.
[0107] Performance test: (1) The flow time of the cement-based grouting material prepared in this embodiment was tested using a 6-cup coating to measure the viscosity / injectability of the grouting material. (2) The 3d compressive strength of the cement-based grouting material prepared in this embodiment was tested according to the "Test Method for Strength of Cement Mortar (ISO Method)" (GB / T 17671-2021). The test results are shown in Table 8:
[0108] Table 8
[0109] .
[0110] Example 9
[0111] A low-viscosity and high-strength cement-based grouting material and a preparation method thereof, comprising the following steps:
[0112] 1. Preparation of micro-nano coagulant:
[0113] (i) Mix dihydrate gypsum and clean water in a ratio of 37 g:100 mL and stir evenly to obtain a turbid liquid for later use.
[0114] (ii) γ-aminopropyltriethoxysilane, polycarboxylic acid dispersant (maleic acid-acrylic acid copolymer (MA / AA)), and 10% by mass aluminum sulfate solution are mixed in a mass ratio of 5:1:112 and stirred evenly to obtain a modified solution for later use.
[0115] (iii) Add the modified liquid to the turbid liquid in a molar ratio of 6:1 between the dihydrate gypsum and aluminum sulfate, and then heat to 60°C and stir to react for 12 hours. After completion, filter out the solid product, wash it twice with deionized water, and dry it in an oven at 80°C for 10 hours to obtain a micro-nano coagulant.
[0116] 2. Take the following raw materials: 400 parts by weight of a cementitious material with volcanic ash properties (composed of 350 parts of Portland cement (P·I42.5) and 50 parts of the modified microspheres prepared in Example 1 above), 0.4 parts by weight of the micro-nano coagulant prepared in this example, 3 parts by weight of a polycarboxylate water reducer, and 160 parts by weight of water. First, mix the cementitious material and the micro-nano coagulant evenly, then add the mixed solution formed by the water reducer and water, and stir evenly to obtain the cement-based grouting material.
[0117] Performance test: (1) The flow time of the cement-based grouting material prepared in this embodiment was tested using a 6-cup coating to measure the viscosity / injectability of the grouting material. (2) The 3d compressive strength of the cement-based grouting material prepared in this embodiment was tested according to the "Test Method for Strength of Cement Mortar (ISO Method)" (GB / T 17671-2021). The test results are shown in Table 9:
[0118] Table 9
[0119] .
[0120] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still repair the technical solutions recorded in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any repair, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A low-viscosity and high-strength cement-based grouting material, characterized in that: The invention comprises the following components: 300-600 parts by weight of a cementitious material having volcanic ash characteristics, 0.2-0.6 parts by weight of a micro-nano coagulant, 0.25-2% by weight of a water reducing agent of the cementitious material, and a water-cement ratio of 0.4-0.8; wherein: the cementitious material having volcanic ash characteristics comprises silicate cement and modified microspheres, and the modified microspheres account for 10-50% of the mass of the silicate cement; The modified microbeads are prepared by the following method: (1) hydroxylating fly ash microbeads with alkaline solution, adding the obtained fly ash microbeads to a dispersion formed by a silane coupling agent, a dispersant and anhydrous ethanol, separating the solid product, washing and drying, and obtaining the modified microbeads; the mass ratio of the silane coupling agent, the dispersant and the anhydrous ethanol is 1:0.2~0.3:120~150; wherein: the silane coupling agent includes: at least one of γ-methacryloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane and vinyltrimethoxysilane; the dispersant includes: at least one of triethylhexylphosphoric acid and sodium dodecyl sulfate; The micro-nano coagulant is prepared by the following method: (i) gypsum and alkali solution are mixed evenly to form a turbid liquid; (ii) a silane coupling agent, a dispersant, and an aluminum sulfate solution are mixed to form a modified liquid; (iii) the modified liquid is added to the turbid liquid and stirred to react, and after completion, a solid product is separated, washed, and dried to obtain the micro-nano coagulant.
2. The low-viscosity and high-strength cement-based grouting material according to claim 1, characterized in that: In step (1), the treatment method is: mixing the fly ash microbeads with alkaline solution and then keeping the mixture warm under heating conditions; after the mixture is mixed, the fly ash microbeads are separated, washed and then dried.
3. The low-viscosity and high-strength cement-based grouting material according to claim 2, characterized in that: The ratio of the fly ash microbeads to the alkali solution is 1g:6-10ml.
4. The low-viscosity and high-strength cement-based grouting material according to claim 2, characterized in that: The alkali solution includes at least one of sodium hydroxide and potassium hydroxide.
5. The low-viscosity and high-strength cement-based grouting material according to claim 2, characterized in that: The concentration of the alkali solution is 0.1-0.5 mol / L.
6. The low-viscosity and high-strength cement-based grouting material according to claim 2, characterized in that: The heating temperature is 40~45℃ and the insulation time is 1.5~2h.
7. The low-viscosity and high-strength cement-based grouting material according to claim 1, characterized in that: In step (1), the ratio of the fly ash microbeads to the dispersion liquid is 1 g: 10-20 ml.
8. The low-viscosity and high-strength cement-based grouting material according to claim 1, characterized in that: In step (i), the ratio of gypsum to alkali solution is 37g:100-120ml.
9. The low-viscosity and high-strength cement-based grouting material according to claim 1, characterized in that: In step (i), the alkali solution includes at least one of sodium hydroxide and potassium hydroxide; the mass fraction of the alkali solution is 0.4-0.6%.
10. The low-viscosity and high-strength cement-based grouting material according to claim 1, characterized in that: In step (ii), the mass ratio of the silane coupling agent, the dispersant and the aluminum sulfate solution is 4-6:1:105-115.
11. The low-viscosity and high-strength cement-based grouting material according to claim 1, characterized in that: In step (ii), the mass fraction of the aluminum sulfate solution is 10-15%.
12. The low-viscosity and high-strength cement-based grouting material according to claim 1, characterized in that: In step (ii), the silane coupling agent includes at least one of vinyl triethoxysilane, γ-aminopropyl triethoxysilane, and octadecyl trimethoxysilane.
13. The low-viscosity and high-strength cement-based grouting material according to claim 1, characterized in that: In step (ii), the dispersant comprises at least one of a polycarboxylic acid dispersant and hydroxyethylidene diphosphonic acid.
14. The low-viscosity and high-strength cement-based grouting material according to claim 1, characterized in that: In step (iii), the modified liquid is added to the turbid liquid in a molar ratio of gypsum to aluminum sulfate of 6:
1.
15. The low-viscosity and high-strength cement-based grouting material according to claim 1, characterized in that: In step (iii), the stirring reaction temperature is 55-65° C. and the time is 11-13 h.
16. The low-viscosity and high-strength cement-based grouting material according to any one of claims 1 to 15, characterized in that: The silicate cement includes: silicate cement is at least one of P·I 42.5 and P·I 52.5R.
17. The low-viscosity and high-strength cement-based grouting material according to any one of claims 1 to 15, characterized in that: The water reducer includes at least one of a naphthalene-based water reducer, a polycarboxylic acid-based water reducer, and a melamine-based water reducer.
18. The method for preparing the low-viscosity and high-strength cement-based grouting material according to any one of claims 1 to 17, characterized in that: The method comprises the following steps: uniformly mixing the gelling material with volcanic ash characteristics and the micro-nano coagulant; then adding a mixed liquid formed by the water reducer and water, and uniformly stirring to obtain the cement-based grouting material.
Citation Information
Patent Citations
Early-strength water reducing agent as well as preparation method and application thereof
CN114195952A
Cement-based grouting material based on carbon nanotube coated fly ash modification and preparation method thereof
CN116789406A
Cited By
Design method of high-performance grouting material accurately matched with physical property structure of soft coal rock
CN120954577A